2023
DOI: 10.1039/d3ra03841f
|View full text |Cite
|
Sign up to set email alerts
|

Novel flurbiprofen clubbed oxadiazole derivatives as potential urease inhibitors and their molecular docking study

Sajjad Ahmad,
Momin Khan,
Aftab Alam
et al.

Abstract: Synthesis of flurbiprofen based oxadiazole derivatives as potent urease inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The clinical value of heterocyclic compounds captures interest in the synthesis of novel compounds and the investigation of their pharmacological characteristics. [6][7][8] Medicinal chemists are unceasingly working to discover the pharmacological potential of heterocycles in which benzothiazoles are stimulating forecasts. [9] It has been established that the endocyclic sulfur and nitrogen activities in the heterocyclic nucleus are essential for various biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical value of heterocyclic compounds captures interest in the synthesis of novel compounds and the investigation of their pharmacological characteristics. [6][7][8] Medicinal chemists are unceasingly working to discover the pharmacological potential of heterocycles in which benzothiazoles are stimulating forecasts. [9] It has been established that the endocyclic sulfur and nitrogen activities in the heterocyclic nucleus are essential for various biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Likewise, Momin et al, reported the synthesis with α-amylase inhibitory activity of flurbiprofen based oxadiazoles, [19] while Sajjad with his team members reported the synthesis and urease inhibition activity of novel derivatives with excellent results. [18,34] Inaddition, our group have reported the synthesis, α-glucosidase inhibition, [21] analgesic and anti-inflammatory activities [35] of novel derivatives of the drug flurbiprofen.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemistry calculations were performed to gain a better understanding of the molecular geometry and electronic properties of the most active molecules. The density functional theory (DFT) method conjugated to the 6-311G(d,p) basis set was used for all calculations using Gaussian 09 software ( Ahmad et al, 2023a , Ahmad et al, 2023b , Frisch et al, 2009 ). The absence of imaginary frequencies was checked to confirm the fundamental states.…”
Section: Methodsmentioning
confidence: 99%